The use of the fungus Dichomitus squalens for degradation in rotating biological contactor conditions - Novotný, Ceněk; Trošt, Nina; Šlušla, Martin; Svobodová, Kateřina; Mikesková, Hana; Válková, Hana; Malachová, Kateřina; Pavko, Aleksander (Bioresource technology, 2012)
Biodegradation potential of Dichomitus squalens in biofilm cultures and rotating biological contactor (RBC) was investigated. The fungus formed thick biofilms on inert and lignocellulosic supports and exhibited stable activities of laccase and manganese peroxidase to reach 40-62 and 25-32% decolorization of anthraquinone Remazol Brilliant Blue R and heterocyclic phthalocyanine dyes, respectively. The decolorization ceased when glucose concentration dropped to 1 mmol l(-1). In RBC reactor, respective decolorizations of Remazol Brilliant Blue R and heterocyclic Methylene Blue and Azure B dyes (50 mg l(-1)) attained 99%, 93%, and 59% within 7, 40 and 200 h. The fungus exhibited tolerance to coliform and non-coliform bacteria on rich organic media, the inhibition occurred only on media containing tryptone and NaCl. The degradation efficiency in RBC reactor, capability to decolorize a wide range of dye structures and tolerance to bacterial stress make D. squalens an organism applicable to remediation of textile wastewaters.
Keywords: Biodegradation, Environmental; rotace; čištění vody; Bioreactors; Coloring Agents; Water Purification; Rotation; biodegradace; Naphthalenesulfonates; naftalensulfonany; barvicí látky; chemické látky znečišťující vodu; Basidiomycota; barva; bioreaktory; Water Pollutants, Chemical; Color